Analisis Sistem Akuntansi Persediaan Bahan Baku Dalam Mengendalikan Persediaan - Pitriyani Pitriyani; Evi Martaseli; Tina Kartini (Universitas PGRI Madiun, 2021)
The purpose of this study was to determine and explain the method of recording inventory, the application of the accounting system for raw material inventory, and inventory control carried out at pada PT. YYY In this study, the data obtained by the researcher used a qualitative descriptive method. This study uses primary data and secondary data where the data is carried out by direct research into the field and also uses library research.The results of the analysis show that found differences regarding the method used by the company with theory, the unit was in accordance with theory and no differences were found regarding the application of systems and procedures related to the inventory accounting system and related functions in the existing raw material inventory. theory and there are additional functions, namely warehouse functions, production, shipping and purchasing. However, there are multiple functions and there is often a mutation of goods without supporting documents and using only verbal at PT. YYY.